Evaluation of startup public support in the Czech Republic and Israel - Svatoň, Martin; Escobar Rios, Andrea; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
The government plays a key role in the startup development by creating a supportive environment that encourages companies in their very beginnings and even expansion abroad. This diploma thesis aims to determine significant factors of Czech startup public support in order to draw implications that could improve startup practices in the Czech environment based on the example of Israel. Findings of secondary research are summarized in form of SWOT analyses to give a comprehensive view of public startup support in both countries from already published data, such as annual reports, statistics from public institutions, and independent reports. The primary research is conducted in the qualitative research through semi-structured interviews with ten stakeholders of the Czech startup scene. The main aim is to verify the information discovered during the secondary research in order to increase the credibility of the exploration. The national system of Czech startup public support is fragmented. This leads to the inefficient allocation of public resources and also to the weak connection of entities. Moreover, the involvement of Czech startups in European programs is not improving. In contrast, Israel has a unified and transparent national system in place with regular adaptations according to current trends. Although it remains institutionally very similar to the Czech Republic, there can be observed much better interconnection of Israeli institutions, leading to greater clarity of available programs and higher success on a global scale. Three implications are developed to tackle these factors. First, it is proposed to establish a system of publicly supported incubators in connection to private sector. Second, reduce the number of supported accelerators and science parks. Third, better use the potential of European programs.
Vedoucí práce: Andrea Escobar Rios
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses